Kolaborasi Stakeholder Dalam Reforma Agraria Dengan Pola Redistribusi Tanah di Kabupaten Hulu Sungai Selatan - Lina Triandaru; Muslih Amberi; Tomi Oktavianoor; Mohammad Fajar Hidayat (Department of Public Administration, Muhammadiyah University of Makassar, 2021)
Presidential Regulation Number 86 of 2018 concerning Agrarian Reform (Perpres No.86 of 2018) explains that asset management consists of land redistribution and asset legalization. Land redistribution consist of asset reform and access reform. In 2019, the Land Office of Hulu Sungai Selatan Regency, South Kalimantan achieved 100% asset reform realization and was awarded the office with the best achievement in the province. The purpose of this study is to identify and explain the implementation of land redistribution with collaboration theory, which is an effort to unite various actors both individuals and organizations to achieve common goals. This research uses a descriptive qualitative approach. Determination of informants was carried out using the purposive sampling technique. Data obtained through interviews and document study. The results showed that the implementation of land redistribution agrarian reform in Hulu Sungai Selatan Regency in 2019 was influenced by several factors: (a) political will from the ruling elite and strong commitment from the government; (b) the government / bureaucratic elite must be separate from the business elite; (c) Police and Satpol PP support; (d) participation of all stakeholders including People's / Peasant Organizations; (e) availability of complete data and information; and (f) thorough and gradual preparation. All of these can solve all implementation constraints in land redistribution in Hulu Sungai Selatan Regency. Peraturan Presiden Nomor 86 Tahun 2018 tentang Reforma Agraria (Perpres No. 86 Tahun 2018) menjelaskan bahwa penataan aset terdiri dari redistribusi tanah dan legalisasi aset. Redistribusi tanah terdiri dari penataan asset dan penataan akses. Kantor Pertanahan Kabupaten Hulu Sungai Selatan, Propinsi Kalimantan Selatan pada tahun 2019 berhasil mencapai realisasi penataan sebesar 100% dan berhasil memenangkan penghargaan sebagai kantor yang mempunyai pencapaian terbaik pada propinsi tersebut. Tujuan dari penelitian ini adalah untukmengidentifikasi dan menjelaskan pelaksanaan reforma agraria dengan teori kolaborasi sebagai upaya penyatuan berbagai pihak baik individu maupun organisasi untuk mencapai tujuan yang sama. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan penentuan informan bersifat purposif. Data diperoleh dari proses wawancara dan studi dokumen. Hasil penelitian menunjukkan bahwa dalam keberhasilan pelaksanaan redistribusi tanah di Kabupaten Hulu Sungai Selatan Tahun 2019 dipengaruhi oleh beberapa faktor diantaranya (a) kemauan politik dari elit penguasa dan komitmen yang kuat dari pemerintah; (b) elit pemerintahan/birokrasi harus terpisah dari elit bisnis; (c) dukungan Kepolisian dan Satpol PP; (d) partisipasi semua stakeholder termasuk Organisasi Rakyat/Tani; (e) ketersediaan data dan informasi yang lengkap; dan (f)persiapan yang matang dan bertahap. semua itu dapat menyelesaikan semua kendala pelaksanaan dalam redistribusi tanah di Kabupaten Hulu Sungai Selatan.